Central Neuropathic Pain in a Patient with Multiple Sclerosis Treated Successfully with Topical Amitriptyline - David J. Kopsky; Remko Liebregts; Jan M. Keppel Hesselink (Case Reports in Medicine)
Central neuropathic pain in patients with multiple sclerosis (MS) is a common debilitating symptom, which is mostly treated with tricyclic antidepressants or antiepileptics. Unfortunately, the use of these drugs is often limited due to adverse events. We investigated the analgesic effect of topical amitriptyline 5% and 10% cream in a patient with central neuropathic pain due to MS. The analgesic effect of topical amitriptyline cream on neuropathic pain was dose related. To evaluate whether this analgesic effect is due to the active compound or placebo, we conducted a double-blind placebo-controlled n-of-1 study with amitriptyline 5% cream and placebo. The instruction was to alternate the creams every week following the pattern ABAB, with an escape possibility of amitriptyline 10% cream. The result was a complete pain reduction after application of cream B, while most of the time cream A did not reduce the pain. The patient could correctly unblind both creams, determining B as active. She noted that in the week of using the active cream no allodynia was present, with a carryover effect of one day.